The influence of implant–abutment connection on the screw loosening and microleakage - Katsuhiro Tsuruta; Yasunori Ayukawa; Tatsuya Matsuzaki; Masafumi Kihara; Kiyoshi Koyano (International Journal of Implant Dentistry, 2018)
Abstract Background There are some spaces between abutment and implant body which can be a reservoir of toxic substance, and they can penetrate into subgingival space from microgap at the implant–abutment interface. This penetration may cause periimplantitis which is known to be one of the most important factors associated with late failure. In the present study, three kinds of abutment connection system, external parallel connection (EP), internal parallel connection (IP), and internal conical connection (CC), were studied from the viewpoint of microleakage from the gap between the implant and the abutment and in connection with the loosening of abutment screw. Methods We observed dye leakage from abutment screw hole to outside through microgap under the excessive compressive and tensile load and evaluated the anti-leakage characteristics of these connection systems. Results During the experiment, one abutment screw for EP and two screws for IP, out of seven samples in each group, were fractured. After the 2000 cycles of compressive tensile loadings, removal torque value (RTV) of abutment screw represented no statistical differences among three groups. Standard deviation was largest in the RTV of EP and smallest in that of CC. The results of microleakage of toluidine blue from implant–abutment connection indicated that microleakage generally increased as loading procedure progressed. The amount of microleakage was almost plateau at 2000 cycles in CC, but still increasing in other two groups. The value of microleakage greatly scattered in EP, but the deviation of that in CC is significantly smaller. At 500 cycles of loading, there were no significant differences in the amount of microleakage among the groups, but at 1000, 1500, and 2000 cycles of loading, the amount of microleakage in CC was significantly smaller than that in IP. Throughout the experiment, the amount of microleakage in EP was largest, but no statistical difference was indicated due to the high standard deviation. Conclusions Within the limitation of the present study, CC was stable even after the loading in the RTV of abutment screw and it prevented microleakage from the microgap between the implant body and the abutment, among the three tested connections.